Importance of bandwidth selection for time delay estimation involving leak detection in buried water plastic pipes - Ayala, Pedro Christian (2018)
A major problem in water companies is to detect leaks in underground pipes as water is a limited source. For many years, acoustics techniques have been used to reduce this problem enhancing leak detection positioning estimation. The correlation of leak noise signals is one of these techniques. Moreover, using the time difference of the arrival of the leak noise at the sensors, and knowledge of the speed at which the noise propagates in the pipe, the distance of the leak from one of the sensor positions can be estimated. This paper describes the importance of the bandwidth selection in the estimation of the time delay. Experimental cases from a test rig in Brazil are shown to support.